On the path of gene expression: a pedagogical proposal for teaching Biology (Research, Society and Development, 2020)
Despite a science widely present in everyday life, most students have difficulties in promoting the correlation and visualization of the applications of the contents covered in the subject of molecular genetics. This makes it difficult to build and consolidate the knowledge that encompasses the contents related to this area of knowledge, making them abstract and distant from your reality. Among the alternatives to facilitate the teaching process, we highlight the diversification of didactic modalities, such as the realization of practical classes, didactic models, application of games, and audiovisual resources, as they contribute to arouse the interest and motivation of students. Thus, due to the recurring difficulties about learning the content of gene expression, the pedagogical proposal “On the path of gene expression”, was developed to optimize the teaching-learning process of this content. For this purpose, the method was structured in two stages, the first one presenting the sequences of the processes and contemplating important concepts, through a fun strategy that consists of the application of a didactic Ludo game. In the second stage, students are encouraged to review the content covered during the first moment and to collaborate through discussions and knowledge sharing so that they can solve the proposed challenge. The objective is to present a teaching method that can assist in understanding the process of gene expression, and it is expected that after the integration of this practice, the concepts will be assimilated more effectively and palpably, especially concerning the topics of sequences and subcellular location of gene products.